2017
DOI: 10.18632/oncotarget.15454
|View full text |Cite
|
Sign up to set email alerts
|

Autologous transplantation of cytokine-induced killer cells as an adjuvant therapy for hepatocellular carcinoma in Asia: an update meta-analysis and systematic review

Abstract: BackgroundHigh recurrence rate after curative treatment is the major problem for hepatocellular carcinoma (HCC). Cytokine-induced killer cells (CIKs) therapy was extensively studied among HCC patients. However, the value of CIKs therapy was controversial. A meta-analysis was performed to investigate the efficacy of adjuvant CIKs after invasive treatments among HCC patients.MethodsWe searched online for literatures studying sequential CIKs therapy for HCC patients. Recurrence-free survival (RFS), progress-free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…This showed an improvement of 14 mo in recurrence free survival[83]. A systematic review and meta-analysis of CIK cell therapy in HCC in Asia reached similar conclusions that in selected patients, progression free survival and recurrence free survival are improved[84].…”
Section: Current and Future Immunotherapeutic Strategies In Hccmentioning
confidence: 88%
“…This showed an improvement of 14 mo in recurrence free survival[83]. A systematic review and meta-analysis of CIK cell therapy in HCC in Asia reached similar conclusions that in selected patients, progression free survival and recurrence free survival are improved[84].…”
Section: Current and Future Immunotherapeutic Strategies In Hccmentioning
confidence: 88%
“…Recently, another RCT also showed that CIK cell treatment significantly increased time-to-recurrence after curative resection [ 34 ]. A recent meta-analysis involving 12 RCTs evaluating the efficacy of adjuvant autologous CIK cell treatment showed that CIK cell treatment significantly prolonged both RFS (pooled HR 0.56; 95% CI 0.47–0.67) and OS (HR 0.59; 95% CI 0.46–0.77) although heterogeneity was moderate (both I 2 = 48%) [ 35 ]. Among eight RCTs that evaluated RFS as an endpoint, seven trials demonstrated that CIK cell treatment significantly improved RFS with HRs ranging from 0.14 to 0.63 [ 2 , 15 17 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivity analysis was conducted to evaluate the consistency of the results and evaluate the influence of single studies on overall risk estimate. 23 …”
Section: Methodsmentioning
confidence: 99%